The implementation of the Regional Development Plan policy focuses on developing the potential of empowered villages in Batu City - Hayat, Hayat; Rudianto, Rudianto; Muchsin, Slamet; Afifuddin, Afifuddin (Universitas Muhammadiyah Ponorogo, 2024)
Rural development aims to enhance the well-being and quality of life of rural communities and reduce poverty through the provision of basic needs, infrastructure development, local economic growth, and sustainable utilization of natural resources and the environment. To achieve these goals, the Village Law implements two approaches, namely